Family sucession in rural properties: A study of the succession situation among academics of UFFS Agronomy Course Erechim and their parents - Paula, S.; Moreira, A. B.; Mota, D. A. (Scientific Electronic Archives, 2017)
Among the numerous studies dealing with the issue of family succession, the majority cities the succession process as a key issue in social reproduction and perpetuation of family farms. Thus, the study aimed to identify the actual situation among academics of UFFS Agronomy Course and their parents when the topic family succession is placed in focus. The methodology used was the application of a structured survey prepared in order to answer the doubts. The survey was designed in online way being sent an access link to the e-mail address previously, and then collected from every academic who had links with the countryside. For others, it was printed, delivered, and then collected. The data were analyzed using descriptive statistics. As a result was obtained that even though there are differences of opinion, the vast majority of young people show comfortable in become a farmer and to continue the current business of the parents. Over 83% of men and 92% of women in the parent class intend to hold family succession still alive, and the children respect this opinion giving autonomy to the parents to carry out the succession when they consider most appropriate. Keywords: family succession, family farming, youth